2021
DOI: 10.1016/j.aap.2021.106142
|View full text |Cite
|
Sign up to set email alerts
|

Safer spaces: The impact of a reduction in road fatalities on the life expectancy of South Africans

Abstract: In this paper we determine the cost of fatalities resulting from road traffic injuries (RTIs) in South Africa. We express the costs in terms of reduced life expectancy and years of potential life lost (YPLL). Our main data source is the Injury Mortality Survey, a retrospective descriptive study carried out in 2009 in South Africa. Using the mortality rates by sex and age from the mortuary data we calculate actual life expectancy at birth. In our counterfactual analysis we assume a reduction of 15% reduction pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, lack of strict enforcement results in no improvement towards road safety. Several studies highlighted that bringing road user behavioural change would help in reducing the deaths due to road crashes (Abreu and Hoeffler, 2021;Ali et al, 2019). Few studies suggested changing social norms in road usage, making it more people centric than vehicular centric would also help in improving safety.…”
Section: Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lack of strict enforcement results in no improvement towards road safety. Several studies highlighted that bringing road user behavioural change would help in reducing the deaths due to road crashes (Abreu and Hoeffler, 2021;Ali et al, 2019). Few studies suggested changing social norms in road usage, making it more people centric than vehicular centric would also help in improving safety.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Lastly, policy implications are discussed followed by conclusion and limitation of the paper. Abreu and Hoeffler (2021) studies the gain in life expectancy with reduction in road fatalities for South Africa. The study highlighted that men accounts for almost 76% of the road fatalities and reduction in traffic fatalities would increase their life expectancy by 0.85 years.…”
Section: Introductionmentioning
confidence: 99%